CONDIÇÂO CRÔNICA DE SAÚDE: PERCEPÇÕES DE CRIANÇAS E ADOLESCENTES: Chronic condition: perceptions of children and adolescents - Irmgard Bärtschi GabatzI, Ruth; Milbrat Marten, Viviane; da Costa Bório, Taniely; Specht, Ana Lúcia; STRAGLIOTTO BAZZAN, JESSICA; da Graça Corso da Motta, Maria (Journal of Health Care, 2022)
Objective: to know the perception of children and adolescents about their chronic health conditions. Materials and methods: This is an exploratory descriptive research with a qualitative approach carried out in the southern region of Brazil. Ten children and adolescents with chronic illness participated in the research, and the information was produced through a dynamic of the Sensitive Creative Method. Data analysis took place through thematic analysis. Results: children and adolescents perceive the chronic disease associated with positive sensations such as interpersonal relationships, games and activities, but also negative sensations such as pain and sadness. Thus, they live in challenging situations in relation to their health conditions, which impose the need for adjustments in their routines and habits. Conclusion: It is concluded that illness is not a simple process for both the child/adolescent and their families, but as the experience experienced, medical procedures become part of the routine and, thus, more easily accepted. In this sense, it is essential that health and education services are equipped to fully assist this population, minimizing suffering and stigma.